Understanding the food preferences of people of low socioeconomic status. (August 2019) - Baumann, Shyon; Szabo, Michelle; Johnston, Josée
Scholars have long studied consumer taste dynamics within class-stratified contexts, but relatively little attention has been paid to the taste preferences of low-socioeconomic-status groups. We analyze interview data from 254 individuals from 105 families across Canada to explore the cultural repertoires that guide low-socioeconomic-status consumer tastes in food. Empirically, we ask which foods respondents prefer, and for what reasons, across socioeconomic status groups. Analytically, we argue that low-socioeconomic-status respondents demonstrate aesthetic preferences that operate according to four cultural repertoires that are distinctly different from that of high-socioeconomic-status omnivorous cultural consumption. Our respondents display tastes for foods from corporate brands, familiar "ethnic" foods, and foods perceived as healthy. While low-socioeconomic-status taste preferences in food are shaped by quotidian economic constraints – what Bourdieu called "tastes of necessity" – we show how cultural repertoires guiding low-socioeconomic-status tastes relate to both material circumstances and broader socio-temporal contexts. Our findings advance debates about the nature of low-socioeconomic-status food ideals by illuminating their underlying meanings and justifications and contribute to scholarly understanding of low-socioeconomic-status consumption.